The Immune Subtype Contributes to Distinct Overall Survival for Ovarian Cancer Patients With Platinum-Based Adjuvant Therapy - Li, Yueyi; Wang, Hang; Chen, Ming; Ma, Xuelei (Frontiers in Immunology, 2022)
Objective: Platinum-based adjuvant therapy is the first-line treatment for ovarian cancer, but the efficacy of the tumor microenvironment to treatment remains unclear. Method: We integrated 565 ovarian cancer samples from two datasets and obtained the immune subtypes (ISs) by consistent clustering of 1190 immune-related gene expressions. Log-rank test and proportional hazards regression models were used to assess the association between ISs and prognosis of platinum-based adjuvant therapy including progression-free survival (PFS) and overall survival (OS). The prognostic contribution of ISs was validated in three additional cohorts. Non-parametric tests were used to assess genomic characteristics, the proportion of immune cells, and immune-related signatures differences among ISs. Results: We identified and validated five ISs associated with different clinical outcomes in platinum-based adjuvant therapy in ovarian cancer patients. These differences were only found in overall survival rather than progression-free survival. An immune subtype had the worst overall survival. An immune subtype had the worst overall survival. These patients mainly derived from the mesenchymal subtype had the lowest tumor purity with a high leukocyte fraction and stromal fraction and had the highest TGF-β response signaling. By contrast, an immune subtype characterized by immunoreactive status with the highest CD8+T cell infiltration and elevated IFN-γ response signaling had the best prognosis. Other subtypes with more diverse immunologic features such as lowest macrophage regulation signaling showed intermediate prognoses. Notably, the contribution of ISs to overall survival was independent of the clinical response to platinum-based drugs. Conclusion: Our analysis revealed the association between different immune characteristics and platinum-based adjuvant therapy, and reminded combining ISs could optimize treatment strategy for patients.